Implementation Of Nursing Management Functions By Nurse Managers During The Covid-19 Pandemic: A Qualitative Study - Tombong, Andi Baso; Gaffar, Indra; Rahman, Framita (Jambura Nursing Journal, 2026)
During challenging periods such as the COVID-19 pandemic, the role of nurse managers in applying core management functions becomes increasingly vital. Despite this, there remains a lack of research exploring how these functions are implemented in crisis settings. This qualitative study, using a phenomenological approach, involved nurse managers from hospitals in South Sulawesi Province that provided inpatient care for COVID-19 patients. Participants were selected through purposive sampling, and data were collected via semi-structured interviews. Thematic analysis revealed three main themes and eight subthemes that reflect the lived experiences of nurse managers during the pandemic. The findings indicate that management practices were necessarily flexible, evolving in response to the unpredictable nature of the pandemic. The organizing function was particularly prominent, as nurse managers had to address urgent issues such as staffing shortages and the reconfiguration of treatment spaces. The study also highlights the importance of strengthening nurse managers’ skills in cross-sector collaboration and coordination, which proved essential in navigating the complexities of pandemic response. These insights offer practical guidance for nurse managers and healthcare institutions in preparing for future crises, emphasizing the need for adaptable management strategies and enhanced interprofessional cooperation.